2021
DOI: 10.3389/fnhum.2021.723728
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of Education on Cognitive Functioning Depend on Clinical Status and Neuropathological Severity

Abstract: Background: Variability in cognitive functions in healthy and pathological aging is often explained by educational attainment. However, it remains unclear to which extent different disease states alter protective effects of education. We aimed to investigate whether protective effects of education on cognition depend on (1) clinical diagnosis severity, and (2) the neuropathological burden within a diagnosis in a memory clinic setting.Methods: In this cross-sectional study, we included 108 patients with subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 64 publications
(108 reference statements)
5
12
0
1
Order By: Relevance
“…Although some studies reported age-modified associations between depression and cognition ( 35 , 51 ), in the current study, increased depression symptoms were similarly associated with more cognitive decline among different age groups. Some previous studies reported education-modified associations between depression and cognition ( 36 , 52 ). Similarly, education level moderated associations between depression symptoms and cognition decline were also detected in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies reported age-modified associations between depression and cognition ( 35 , 51 ), in the current study, increased depression symptoms were similarly associated with more cognitive decline among different age groups. Some previous studies reported education-modified associations between depression and cognition ( 36 , 52 ). Similarly, education level moderated associations between depression symptoms and cognition decline were also detected in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Since many studies have indicated that sex and age might be related to cognitive decline and depression (33)(34)(35), sexand age-stratified analyses were also performed. In addition, accumulating evidence suggested that having more years of education is a protective factor for cognitive impairment (36,37); thus, additional analyses stratified by education levels were also conducted to examine the associations in different subgroups. Stata version 15.1 software (Stata Corp, College Station, TX) was used for all analyses.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Recent studies on Alzheimer's disease (AD) have revealed stage‐dependent effects of CR on cognitive function across the AD spectrum. CR's positive effects on cognition are stronger in predementia stages than in dementia stages 15,16 . High CR attenuates the cognitive decline in predementia stages, but accelerates cognitive decline in dementia stages 17 .…”
Section: Introductionmentioning
confidence: 96%
“…CR's positive effects on cognition are stronger in predementia stages than in dementia stages. 15,16 High CR attenuates the cognitive decline in predementia stages, but accelerates cognitive decline in dementia stages. 17 For WMH subjects, Zahodne et al 18 showed that education mitigated the effect of WMH on cognitive function in subjects at lower risk for dementia, but exacerbated the effect in those at higher risk for dementia.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported to have exceptional performance relative to other traditional ML programs. MRI is a medical imaging diagnostic program that is safe, non-invasive, non-persistent, and pain-free (32,33). Unlike CT and other imaging, MRI is not associated with radiation (34); rather, it uses a uniform magnetic field and radio-frequency to display the internal system of the human body.…”
Section: Discussionmentioning
confidence: 99%